2023
DOI: 10.31258/jamt.4.1.18-23
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Physical and Mechanical Properties of Asphalt by Addition of Low-cost Few-layers Graphene (FLG)

Abstract: Physical and mechanical properties of asphalt have been improved by adding of few-layers graphene (FLG). FLG was obtained from a simple, low-cost and environmentally friendly liquid shear exfoliation method using a kitchen blender. The melted asphalt at temperature of 150oC was mixed with FLG at various concentrations (10 mg/ml, 20 mg/ml and 30 mg/ml) and contents (0 wt%, 3 wt%, 6 wt%, and 9 wt%) by weight of asphalt. The homogenized mixture was taken for penetration and softening point tests, while the mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…It can be seen that, generally the penetration values decrease (or asphalt hardness increase) linearly with the increase of weight percentage of WPB in asphalt. These tendence was observed with FLG addition in asphalt by (Amri et al, 2023). These results suggest that the mechanical behavior of the asphalt-WBP mix will very quickly be dominated by the properties of the WBP, especially above 20% doping.…”
Section: Asphalt Penetration Analysismentioning
confidence: 65%
See 4 more Smart Citations
“…It can be seen that, generally the penetration values decrease (or asphalt hardness increase) linearly with the increase of weight percentage of WPB in asphalt. These tendence was observed with FLG addition in asphalt by (Amri et al, 2023). These results suggest that the mechanical behavior of the asphalt-WBP mix will very quickly be dominated by the properties of the WBP, especially above 20% doping.…”
Section: Asphalt Penetration Analysismentioning
confidence: 65%
“…From a flow perspective, the binder rate of 6.2% remains a good value for the formulation of asphalt concrete. (Amri et al, 2023) found that the asphalt concrete flow value increases with the increase in FLG content, with an average increase of around 3.5% to 17.7% compared to conventional asphalt without the addition of FLG which has a ow value of 3.8 mm. This indicated that, contrary to FLG, WPB causes a decrease in the elasticity of asphalt.…”
Section: Samples Of Asphalt Concretementioning
confidence: 94%
See 3 more Smart Citations